2012
DOI: 10.1093/jjco/hys138
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of CD34 Expression in Gastrointestinal Stromal Tumors is Related to Cystic Degeneration Following Imatinib Use

Abstract: Objective: We evaluated the characteristics of the gastrointestinal stromal tumors that showed discrepancies between their assessment using the Response Evaluation Criteria in Solid Tumor (RECIST) and Choi's criteria. We also investigated the clinical applicability of Choi's criteria to Korean gastrointestinal stromal tumor patients undergoing imatinib therapy. Methods: Patients with advanced gastrointestinal stromal tumors treated with frontline imatinib were analyzed. Computed tomography images of these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Conversely with the results of Bertucci's analysis, CD34 (+) patients had significantly shorter progression-free intervals for imatinib. This finding was compatible with the result of another study which showed that the tumors which present with a cystic degeneration after imatinib therapy were mostly CD34 (-) tumors (Koh et al, 2012). Therefore, CD34 immunoreactivity seems to be both negative predictive and prognostic factor.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely with the results of Bertucci's analysis, CD34 (+) patients had significantly shorter progression-free intervals for imatinib. This finding was compatible with the result of another study which showed that the tumors which present with a cystic degeneration after imatinib therapy were mostly CD34 (-) tumors (Koh et al, 2012). Therefore, CD34 immunoreactivity seems to be both negative predictive and prognostic factor.…”
Section: Discussionsupporting
confidence: 91%
“…Koh et al reported on discrepancies between RECIST- and Choi-based response in 27/61 patients, who responded to imatinib with cystic degeneration related to lack of CD34 expression after treatment. Choi criteria correlated significantly stronger with progression-free survival (PFS) than RECIST [ 14 ].…”
Section: Imaging Methodsmentioning
confidence: 99%
“…40,41 In this context, loss of KIT expression may be a predictor of disease recurrence. Various morphological changes (such as hypocellularity, hyalinised or myxoid stroma, and necrosis, or a change from spindled to epithelioid or pleomorphic cytomorphology) have been described, and KIT expression may be completely lost, as may CD34.…”
Section: Histologymentioning
confidence: 99%